A CO2/N2-Responsive Pickering Emulsion Stabilized by Novel Switchable Surface-Active Alumina Nanoparticles. (May 2022) - Chen, An; Wang, Duo; Chen, Jingsi; Xu, Jianhong; Zeng, Hongbo
Abstract: This article reports the development of a novel switchable Pickering emulsion with rapid CO2 /N2 responsiveness, which is stabilized using alumina nanoparticles hydrophobized in situ with a trace amount of a switchable superamphiphile via electrostatic interactions. With the introduction of CO2 for 30 s, the Pickering emulsion can be spontaneously demulsified with complete phase separation; the emulsion can then be reconstructed in response to N2 purging for 10 min followed by homogenization. Moreover, the stable Pickering emulsion can be stored for more than 60 days at room temperature without any visible change. The CO2 /N2 -responsive behavior of the switchable Pickering emulsion is attributed to the reversible desorption/adsorption of the switchable surfactants on the surfaces of the alumina nanoparticles upon the alternative bubbling of CO2 or N2 . Thanks to the simple fabrication of the surfactant and the hydrophobization of the alumina nanoparticles, this research has developed an extremely facile and cost-efficient method for preparing a rapidly CO2 /N2 -responsive switchable Pickering emulsion. The dosage of the switchable surfactants has been significantly reduced by nearly 1500 times (from 150 to 0.1 mmol∙L −1 ) as compared with the dosage used in previous studies. Moreover, the as-prepared CO2 /N2 -responsive switchable Pickering emulsion is environmentally friendly, mild, and nontoxic; thus, it holds great potential for practical applications with considerable economic and environmental benefits, such as oil transport, fossil fuel production, environmental gases detection, and the encapsulation and release of active ingredients.